Cytotoxic Activity of Secondary Metabioltic Agent Produce by Actinomycetes - Abbas Hassan, Istbraq; Abdullah Jassim, Yazi; Salman Kadhim Al-Khafaji, Noor (Al-Nahrain Journal of Science, 2026)
In this work, total of 50 samples of different soil types (sandy, loomy, clayey, and river deposits) were collected randomly. The physico-chemical properties such as pH, soil temperature and electrical conductivity of the soil samples were studied and analysed Soil characteristics all were within the limits of growth and reproduction of Actinomycetes. Of the 50 soil samples, only 35 were sourced to obtain 18 colonies, were suspected to be Actinomycetes. These isolates were purified by sub culturing more than one time on International Streptomyces project-2 agar (ISP-2),the pigmentation of the selected colonies exhibited a spectrum of colors ,including shades of white, cream, gray, green ,black to yellow. These isolates were identified by culture properties which showed that they were Gram positive varieties of aerial mycelia and substrate mycelia and spore chain formation. By the third day of incubation, the isolate had attained the stationary phase of its growth cycle.at maximum OD 0.619nm. Extraction of Extracellular secondary metabolites from Each of the Actinomycetes by ethyl acetate. According to the quantity of the product and the speed of its production, 3 isolates (NI- RS 15, AM - AG 18 and MA-CL2) were selected to complete the study. All extracts with high solubility with water, had melting point range 287ºC- 300°C and were powder in natural. Chemical Characterization of secondary metabolites were as follow λ max ranged from 274 nm to 320 nm FTR show several bands of absorption as functional chemical group and HPLC clearly sharp peaks that appeared at 2.1 - 9.9 minutes which indicated a very well separated. The cytotoxicity of extracts were assessed by MTT on normal cell line was which inhibited cells range from 9.9-13.9% in 200 μg / mL.